INVESTIGATION OF WAVE RUN-UP ON AN OVERTOPPING BREAKWATER IN RELATION TO WAVE ENERGY CONVERSION - A. Ildha Dwi Puspita; Muhammad Arsyad Thaha (Journal Of Renewable Energy Engineering, 2026)
Wave run-up on coastal structures plays an important role in overtopping processes, which are relevant to the performance of overtopping wave energy converter (OWEC) systems. This study aims to investigate the characteristics of wave run-up on an overtopping breakwater with a double-slope configuration under regular wave conditions. The experiments were conducted in a two-dimensional wave flume using variations of wave period (0.9 s, 1.1 s, and 1.3 s) and water depth (0.15 m, 0.17 m, and 0.19 m). Wave heights were controlled by adjusting the stroke of a flap-type wave generator, producing waves in the range of 4–6 cm. Wave parameters were analyzed in terms of wave steepness (), while run-up was expressed as relative wave run-up (). The results show that wave steepness has an inverse relationship with relative wave run-up, where lower steepness leads to higher run-up values. Longer wave periods produce greater run-up due to increased wave energy, while shallower water depth enhances run-up due to wave shoaling effects. These findings indicate that wave conditions characterized by low steepness, long periods, and shallow water depth are favorable for increasing wave run-up on overtopping breakwaters, which is beneficial for improving the hydraulic performance of OWEC systems.